2021
DOI: 10.2478/rjim-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Serologic screening and infectious diseases consultation in renal transplant candidates for measles, mumps, rubella and varicella

Abstract: Background: Renal transplant recipients are at increased risk for developing complications of vaccine-preventable diseases. They benefit from a comprehensive pre-transplant evaluation when they might safely receive live vaccines. The primary aim of our study was to investigate the number of renal transplant recipients who were evaluated for serologic status against measles, mumps, rubella (MMR), and varicella. Secondarily, we investigated if pre-transplant Infectious Diseases consultation (IDC) improved vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The value of Infectious Disease consultation or structured programs for screening and catch-up immunization in improving vaccination rates among KT candidates have been demonstrated in other studies, and this was further strengthened by our study. 12,13,18-20 Vaccine acceptance rate was as high as 99% in 1 study, whereas in others, despite ID consultation or structured catch-up immunization programs, there was only a modest increase in immunization rates. 12,13,18,20 We did not have data on reasons for refusal except for a few patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The value of Infectious Disease consultation or structured programs for screening and catch-up immunization in improving vaccination rates among KT candidates have been demonstrated in other studies, and this was further strengthened by our study. 12,13,18-20 Vaccine acceptance rate was as high as 99% in 1 study, whereas in others, despite ID consultation or structured catch-up immunization programs, there was only a modest increase in immunization rates. 12,13,18,20 We did not have data on reasons for refusal except for a few patients.…”
Section: Discussionmentioning
confidence: 78%
“…12,13,18-20 Vaccine acceptance rate was as high as 99% in 1 study, whereas in others, despite ID consultation or structured catch-up immunization programs, there was only a modest increase in immunization rates. 12,13,18,20 We did not have data on reasons for refusal except for a few patients. It is noteworthy that hepatitis A vaccine refusal was common (refused by 15/17 patients who refused vaccination).…”
Section: Discussionmentioning
confidence: 78%
“…A previous study described how infectious disease consultation improved rates of MMRV serological screening and vaccination rates. 18 In our center, the transplant infectious diseases team works closely with the SOT teams to provide guidance and protocols for vaccinations. This highlights the importance of a multidisciplinary approach to improve transplant patient care.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, previous studies showed that these immunity screenings were not routinely done in many transplant centers. 18 Various regimens of MMR and VZV vaccines are recommended by the CDC based on underlying patient conditions. Although the CDC does not have specific MMRV recommendations for pretransplant candidates, 2 doses of MMR vaccines are recommended in patients who do not have immunity against measles or mumps or who were born after 1957.…”
Section: Introductionmentioning
confidence: 99%
“…These consultations may be most effective when linked to universal screening and vaccination protocols. Even with high rates of infectious diseases consultation, one study group identified measles, mumps and rubella serologic screening and vaccination in their transplant candidates as an opportunity for further improvement through protocolization [32 ▪ ,33 ▪ ]. Transplant pharmacist-led vaccination recommendations have also been shown to increase vaccination rates [34].…”
Section: Soft Stopsmentioning
confidence: 99%